Gaya Kepemimpinan Dan Hubungannya Dengan Motivasi Pegawai Di Distrik Navigasi Kelas 1 Dumai - Jannah, Dewi (Musamus Journal of Public Administration, 2024)
This study aims to identify the leadership styles practiced in the Class 1 Navigation District of Dumai. This research also discusses leadership styles and their relationship with employee work motivation within the organization. To achieve the objectives of this study, 100 questionnaires were distributed and used for data analysis. The research instrument consists of 7 items regarding the respondents' background, 70 items to identify leadership styles, and 30 items to identify employee motivation. Data analysis utilized percentages, means, and Pearson correlation. The leadership styles highlighted in this study are the Path Goal Theory leadership styles, which include directing, supporting, participating, and success-oriented, as well as the Normative Theory, which includes Autocratic, Consultative, and Group styles. To study employee motivation, three dimensions were used: emotions, social relationships, and effort (Luthan 1995). The results of the study found that the practiced leadership style leaned more towards the supporting style (Path Goal Theory) with the highest scale of 4.64. However, the lowest scale was the consultative style at 3.86 (Normative Theory). Furthermore, this study found that autocratic leadership practices (Normative Theory) were also emphasized by leaders while still contributing to organizational progress. In addition, the results indicated a strong and significant relationship between leadership styles and employee work motivation, with coefficient values for all characteristics of leadership styles and employee motivation in the Class 1 Navigation District of Dumai.